VIDIO GAMES DAN ISLAM : ANALISIS GAME RUMAH AMALIA - Siregar, Muhammad Shulhi Alhadi (IAIN Padangsidimpuan, 2018)
Marriage records related to the legal consequences of national law to date still reap a lot If someone feels bored and tired, then the first thing they want to do is how to get rid of the boredom. This is most people will be different in doing it, some do touring, sleeping, doing light work, and there are playing vidio games. Player vidio games will feel more fun if they play some games. But how do they choose the game, but they play a game that is not useful and even make them become someone else? Even in religion is also very concerned about the application or media this one, because many concerns generated from the media. So from here some games try to move to issue a more useful game against the player like Amalia House game. The game is understood many different people with other games, this game can get religious lessons for the players.But in some comment fields that are on Playstore, some users provide reviews that the game can make someone close to God and teach the truth. So from this problem the author tries to examine whether the review is worthy to be crowned against the Amalia House game? And the focus of this research is to try to review the background of the Amalia House and the games they produce.The results obtained by researchers is the game Amalia House trying to issue a different game with another game. This game teaches the religion of Islam and fosters independent character for the player, by learning while playing. But the crowning of the Amalia House game can get closer to God and teach the impossible truth, for the reason of seeing the essence of a game that only gives pleasure to the player and the player of a game will never focus on the meaning of the game, but only focuses on how the game is fun or not.